Historical and contemporary reflections on evolutionary concepts that challenge the classification of endo-perio lesions - Kristen Bingham; James L Gutmann (Wolters Kluwer Medknow Publications, 2023)
The so-called endodontic-periodontic lesion or relationship has been a clinical concept that has mystified the dental profession for decades as it relates to accurate, precise diagnoses. It is a typical chicken-before-the-egg type of dilemma imbued with unknowns as to the etiology, interrelationships, and correct procedural management. Attempts have been made over the last 100 years to classify this relationship, with all efforts falling short of ideal in various respects. This article will attempt to provide historical relevance, scientific validity, and some clinical perspectives to this dilemma, including reflections that are encountered daily in contemporary dental practice.